Report of the Committee of Experts on Unemployment Estimates - Planning Commission (Planning Commission, 1970)
The Planning Commission set up a Committee of Experts on Unemployment Estimates under its Resolution No. L & E (E) 12-7/68, dated August 19, 1968 to “go into the estimates of unemployment worked out for the previous Plans and the data and methodology used in arriving at them and advise the Planning Commission on the various issues connected therewith, in particular, the alternative methods of analysis, computation and presentation that may be adopted for the Fourth Five-Year Plan (1969-74) in the ten year perspective of 1969-79.
Planning Commission Government of India